The pathogenic role of epithelial and endothelial cells in early-phase COVID-19 pneumonia: victims and partners in crime - Chilosi, Marco; Poletti, Venerino; Ravaglia, Claudia; Rossi, Giulio; Dubini, Alessandra; Piciucchi, Sara; Pedica, Federica; Bronte, Vincenzo; Pizzolo, Giovanni; Martignoni, Guido; Doglioni, Claudio (Modern pathology, 2021)
Current understanding of the complex pathogenesis of COVID-19 interstitial pneumonia pathogenesis in the light of biopsies carried out in early/moderate phase and histology data obtained at postmortem analysis is discussed. In autopsies the most observed pattern is diffuse alveolar damage with alveolar-epithelial type-II cell hyperplasia, hyaline membranes, and frequent thromboembolic disease. However, these observations cannot explain some clinical, radiological and physiopathological features observed in SARS-CoV-2 interstitial pneumonia, including the occurrence of vascular enlargement on CT and preserved lung compliance in subjects even presenting with or developing respiratory failure. Histological investigation on early-phase pneumonia on perioperative samples and lung biopsies revealed peculiar morphological and morpho-phenotypical changes including hyper-expression of phosphorylated STAT3 and immune checkpoint molecules (PD-L1 and IDO) in alveolar-epithelial and endothelial cells. These features might explain in part these discrepancies.